القراءات القرآنية من التنظير إلى التنظيم؛ بحث في تأصيل الاتجاهات وتطبيقاتها بسورة الفاتحة - al-Aqtash, Abdulhamid (Al-Ḍād Journal, 2020)
This article has two aspects, theoretical and practical. As for the theoretical one, it focuses on the etymology of the science of Quran recitation (Qira’at) and the evolution of it’s tends of directions. It concludes that directing Qira’at is based on the permission of the Prophet Mohammad -peace be upon him- to facilitate the verbal formulations of Qur’an and its recitations, that the narration of the Companions is an argument, that all Arabic dialects are an argument, and that the acceptance of the famous reciters is an argument, but the approval of Qira’at with the classical rules of al-Fusha which changes Quran recitation into current unified system, which are the famous (Hafs) recitation in the east side of Islam world, and (Warsh or Qālūn) recitation in the west side. As for the applied one, it was in the recitation (Qiraat) of Chapter (Surat) al-Fātiḥah, by presenting its data in terms of: the differences, the degree of Qiraat, the class of the reciters, the mode of dialects, and the directing of syntax. The conclusion of this application confirms with the previous theoretical understanding that the prevalence of the linguistic eloquence trend in the organization of general reading, on a unified linguistic case.